2019
DOI: 10.3892/mmr.2019.10395
|View full text |Cite
|
Sign up to set email alerts
|

LINC00978 promotes bladder cancer cell proliferation, migration and invasion by sponging miR‑4288

Abstract: long noncoding rnas regulate the occurrence and progression of numerous types of cancer, including bladder cancer (Bca). However, the role of long intergenic non-protein coding rna 978 (linc00978) in Bca remains unknown. In the present study, it was identified that the LINC00978 expression level was significantly increased in BCa tissues compared with adjacent normal tissues. By performing cell proliferation, colony formation, Transwell and Matrigel assays, it was demonstrated that LINC00978 knockdown signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In tumors of the urinary system, MIR4435-2HG is abnormally upregulated in cancer tissues and cancer cell lines of clear cell renal cell carcinoma and bladder cancer ( 3 , 40 , 41 ). In nervous system tumors, MIR4435-2HG is highly expressed in plasma, cancer tissues and cancer cell lines of glioma ( 42 , 43 ), and in cancer tissues and cancer cell lines of glioblastoma ( Figure 3 ) ( 44 ).…”
Section: Abnormal Regulation and Biological Effects Of Mir4435-2hg In...mentioning
confidence: 99%
See 2 more Smart Citations
“…In tumors of the urinary system, MIR4435-2HG is abnormally upregulated in cancer tissues and cancer cell lines of clear cell renal cell carcinoma and bladder cancer ( 3 , 40 , 41 ). In nervous system tumors, MIR4435-2HG is highly expressed in plasma, cancer tissues and cancer cell lines of glioma ( 42 , 43 ), and in cancer tissues and cancer cell lines of glioblastoma ( Figure 3 ) ( 44 ).…”
Section: Abnormal Regulation and Biological Effects Of Mir4435-2hg In...mentioning
confidence: 99%
“…Here, this article outlines the ceRNA network centered on MIR4435-2HG and its biological significance ( Figure 6 ). MIR4435-2HG can be used as the ceRNA of 20 miRNAs, 19 of which are found in 14 cancers, including miR-22-3p ( 18 ), miR-206-3 ( 1 ), miR-296-5p ( 1 ), miR-497-5p ( 11 ), miR-138-5p ( 53 ), miR-203a-3p ( 13 ), miR-6754-5p ( 25 ), miR-204-5p ( 26 ), miR-528 ( 30 ), miR-202 ( 30 ), miR-125a-5p ( 52 ), miR125b-5p ( 52 ), miR-1224-5p ( 44 ), miR-4288-3p ( 41 ), miR-513a-5p ( 3 ), miR-128- 3p ( 33 ), miR-93-3p ( 45 ), miR-802-5p ( 48 ), and miR-383-5p ( 47 ). In addition, in osteoarthritis, MIR4435-2HG was found to sponge miR-510-3p ( 63 ).…”
Section: The Cerna Network Of Mir44350-2hgmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, accumulating biomarkers are identified for early detection and survival prediction in HCC [ 22–24 ]. Previous studies have suggested that LINC00978 is an oncogenic LncRNA in diverse cancers, like breast cancer [ 25 ], melanoma [ 26 ] and bladder cancer [ 27 ]. Our data presented that LINC00978 was upregulated in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from mediating DNA, RNA, or proteins, LncRNAs also served as a ceRNA of miRNA [ 27 ]. For instance, LINC00978 could facilitate the progression of breast carcinoma via working as a sponger for microRNA-4288.…”
Section: Discussionmentioning
confidence: 99%